2014
DOI: 10.2147/mder.s44063
|View full text |Cite
|
Sign up to set email alerts
|

MRI-conditional pacemakers: current perspectives

Abstract: Use of both magnetic resonance imaging (MRI) and pacing devices has undergone remarkable growth in recent years, and it is estimated that the majority of patients with pacemakers will need an MRI during their lifetime. These investigations will generally be denied due to the potentially dangerous interactions between cardiac devices and the magnetic fields and radio frequency energy used in MRI. Despite the increasing reports of uneventful scanning in selected patients with conventional pacemakers under close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Currently, there is no consensus regarding who should receive an MRI‐conditional pacemaker or ICD. Opinions range from universal adoption to almost complete dismissal . Our results demonstrated that older patients and subjects from emerging countries were less likely to be implanted with an MRI‐compatible device.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, there is no consensus regarding who should receive an MRI‐conditional pacemaker or ICD. Opinions range from universal adoption to almost complete dismissal . Our results demonstrated that older patients and subjects from emerging countries were less likely to be implanted with an MRI‐compatible device.…”
Section: Discussionmentioning
confidence: 80%
“…No validated guideline exists for this subset of patients but asynchronous VOO mode with deactivation of ICD parameters appears to be a reasonable approach [31]. …”
Section: Mri Modesmentioning
confidence: 99%
“…In recent years the use of both magnetic resonance imaging (MRI) and cardiovascular implanted electronic devices has undergone remarkable growth [1,2]. It is estimated that during their lifetime, up to 75% of patients with pacemaker develop a medical condition for which an MRI may be useful or even critically necessary for optimal diagnosis and treatment [3].…”
Section: Introductionmentioning
confidence: 99%